Development of Ash Powder Processing Technique to Ash Pellets with Polyvinyl Alcohol Binder - Kaenchan, Nutchanat; Supakuntadasiri , Maturada; Dejang, Nuchjira (Burapha Science Journal, 2026)
The main purpose of the research is the development of the ash pellet processing for liquid adsorption undering the polyvinyl alcohol binder concentrations of solution percent by mass of 10.7 and 13.8, with various solution additives of 90, 180, 270, and 360 microliters per ash powder of 2 g. The ash powder mixed binder was poured into the mold and compressed for forming the ash pellet with hydronic pressure of 6.7 MPa. The ash pellets had been dried at a temperature of 110oC for 24 hr. The chemical composition of ash has appeared in the SiO2, CCaO3, C2CaO4, CaO2, and amorphous phases. The density and hardness of ash pellets were presented to reduce value while the water adsorption percentage was increased, with binder solution addition. After that, 14 days of soaking the ash pellet, it is still the shape of a pellet. The microstructure of the ash pellet was presented the densely agglomerated ash particles and porous. Therefore, the polyvinyl alcohol binder with concentrations of solution percent by mass 13.8 with a solution addition volume of more than 90 microliters was the optimum condition for mixing with ash powder to produce pellets.